Pengaruh Food Taboo dengan KEK Ibu Hamil - Isnaini Rizki Sabilla; Dewi Woro Astuti; Achmad Djamil (Jurnal Kebidanan dan Keperawatan Medika, 2026)
Food taboo behavior can be influenced by several factors including food knowledge and education because knowledge and education play an important role in decreasing belief in food taboo in pregnant women, one of the consequences of food taboo is the occurrence of KEK in pregnant women. The purpose of this study was to determine the effect of food taboo on the incidence of KEK in pregnant women in Totokarto Village, Adiluwih District, Pringsewu Regency in 2025. The type of quantitative research, pre-experimental design using a one group pretest and posttest design approach. The population and sample in this study were all pregnant women in Totokarto Village, Adiluwih District, Pringsewu Regency for the period January - March 2025, totaling 46 pregnant women. In this study, the sampling technique used was accidental sampling and using the chi-square test. Based on the results of the univariate analysis, it was found that most respondents had good food taboos totaling 24 respondents (52.2%) and most respondents did not experience KEK totaling 26 respondents (56.5%). Based on the results of the statistical test, a p-value of 0.003 was obtained or a p-value <α value (0.05), which means that there is an Influence of Food Taboo on the Incidence of KEK in Pregnant Women in Totokarto Village, Adiluwih District, Pringsewu Regency in 2025. The results of this study are expected to be one of the health information about the importance of food taboo on the incidence of KEK, so that pregnant women must maintain a nutritious diet properly and correctly, so that the nutritional status of the fetus and fetal growth and development are also good, it is recommended that pregnant women always be active in participating in health education in order to get more information about the importance of maintaining nutritional status during pregnancy